De novo assembly of Aureococcus anophagefferens transcriptomes reveals diverse responses to the low nutrient and low light conditions present during blooms - Frischkorn, Kyle R.; Harke, Matthew J.; Gobler, Christopher J.; Dyhrman, Sonya T. (Frontiers in Microbiology, 2014)
Transcriptome profiling was performed on four treatments of the harmful algal bloom-forming pelagophyte Aureococcus anophagefferens strain CCMP 1850 to assess responses to common stressors for dense phytoplankton blooms: low inorganic nitrogen concentrations, low inorganic phosphorus concentrations, low light levels, and a replete control. The de novo assemblies of pooled reads from all treatments reconstructed 54,000 transcripts using Trinity, and 31,000 transcripts using ABySS. Comparison to the strain CCMP 1984 genome showed that the majority of the gene models were present in both de novo assemblies and that roughly 95% of contigs from both assemblies mapped to the genome, with Trinity capturing slightly more genome content. Sequence reads were mapped back to the de novo assemblies as well as the gene models and differential expression was analyzed using a Bayesian approach called Analysis of Sequence Counts (ASC). On average, 93% of significantly upregulated transcripts recovered by genome mapping were present in the significantly upregulated pool from both de novo assembly methods. Transcripts related to the transport and metabolism of nitrogen were upregulated in the low nitrogen treatment, transcripts encoding enzymes that hydrolyze organic phosphorus or relieve arsenic toxicity were upregulated in the low phosphorus treatment, and transcripts for enzymes that catabolize organic compounds, restructure lipid membranes, or are involved in sulfolipid biosynthesis were upregulated in the low light treatment. A comparison of this transcriptome to the nutrient regulated transcriptional response of CCMP 1984 identified conserved responses between these two strains. These analyses reveal the transcriptional underpinnings of physiological shifts that could contribute to the ecological success of this species in situ: organic matter processing, metal detoxification, lipid restructuring, and photosynthetic apparatus turnover.